PENERAPAN BAHAN AJAR DIGITAL BERBASIS HEYZINE FLIPBOOK TERHADAP HASIL BELAJAR KOGNITIF PADA SISWA SMKN 4 BOJONEGORO - Dita Aulia Sunaryo; Nugrahani Astuti; Febriani Lukitasari; Rendra Lebdoyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the implementation of learning, students' cognitive learning outcomes, and students' responses after implementing Heyzine Flipbook-based digital teaching materials on poultry-based dishes at SMKN 4 Bojonegoro. This quantitative study employed a One Group Pretest-Posttest Design (pre-experimental) involving 36 students from Class X Culinary 1 and 35 students from Class X Culinary 2. Data were collected through observation, tests, and questionnaires, and analyzed using quantitative/statistical analysis, the N-Gain test, and the Paired Sample t-Test. The results showed that the learning implementation was categorized as very good. The average score increased from 70.00 to 75.00 in Class X Culinary 1 and from 60.00 to 85.00 in Class X Culinary 2. The Paired Sample t-Test showed a significance value (2-tailed) of <0.001, indicating a significant difference between the pre-test and post-test scores. Students' responses ranged good. Therefore, the implementation of Heyzine Flipbook-based digital teaching materials supported the improvement of students' cognitive learning outcomes.